2020
DOI: 10.1200/jco.2020.38.15_suppl.6569
|View full text |Cite
|
Sign up to set email alerts
|

SNOW: Sitravatinib and nivolumab in oral cavity cancer (OCC) window of opportunity study.

Abstract: 6569 Background: Sitravatinib (receptor TKI against TYRO3, AXL, MERTK and VEGF family of receptors) is predicted to increase M1-type tumor-associated macrophages (TAMs) and decrease MDSCs in the tumor microenvironment. SNOW is a window-of-opportunity study evaluating the immunogenic and antitumor effects of preoperative sitravatinib and nivolumab in patients (pts) with OCC. Early results demonstrated the combination was safe and active (Oliva et al, SITC 2019). Biomarker analyses and updated results are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Their study has demonstrated increased pathological response with combination treatment but without statistical significance (60% vs. 37.5%, p = 0.4) 41 . To further explore the influence of the tumour microenvironment on ICI outcomes in the neoadjuvant setting, Bernal et al investigated adding in sitravatinib, a multi‐target tyrosine kinase inhibitor, with nivolumab pre‐operatively 42 . They theorised that increased density of M1‐type tumour‐associated macrophages and decreased incidence of myeloid‐derived suppressor cells from this combination would amplify treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their study has demonstrated increased pathological response with combination treatment but without statistical significance (60% vs. 37.5%, p = 0.4) 41 . To further explore the influence of the tumour microenvironment on ICI outcomes in the neoadjuvant setting, Bernal et al investigated adding in sitravatinib, a multi‐target tyrosine kinase inhibitor, with nivolumab pre‐operatively 42 . They theorised that increased density of M1‐type tumour‐associated macrophages and decreased incidence of myeloid‐derived suppressor cells from this combination would amplify treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…They theorised that increased density of M1‐type tumour‐associated macrophages and decreased incidence of myeloid‐derived suppressor cells from this combination would amplify treatment response. In 10 patients they demonstrated a greater disease response in those with a higher percentage of PD‐L1 positive tumour‐associated macrophages 42 . Whether this combination alone leads to survival improvements is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 The study found that sitravatinib monotherapy resulted in a less immunosuppressive TME and was associated with macrophage repolarization toward the M1 type in patients who responded to sitravatinib with nivolumab. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%